Private biological reserves as carbon sinks: aboveground biomass estimation in the Tirimbina Biological Reserve, Costa Rica - Nectaly Mejia, Levy (2026)
This study assessed aboveground biomass and carbon storage potential in six permanent plots of mature tropical rainforest located in the Tirimbina Biological Reserve, Sarapiquí, Costa Rica. Three allometric equations were applied, and floristic composition was analyzed using the Importance Value Index (IVI). Results show that the estimated biomass falls within the range reported for mature neotropical forests. Equations incorporating diameter, total height, and wood basic density provided more robust estimates in structurally complex ecosystems. The IVI analysis revealed that a few species, particularly Pentaclethra macroloba, concentrate a significant portion of the ecological and structural importance of the forest. This suggests that IVI may complement biomass assessments by identifying species contributing most to carbon storage. However, the integration of dominant species into management or restoration strategies should be aligned with conservation and ecosystem functionality goals, as some species, despite their dominance, may not hold commercial or priority management value. These findings underscore the relevance of biological reserves as long-term ecological research sites, providing key information for climate change mitigation and adaptation policies in the neotropics.